Deixis between Traditional and Modern Scholars: A Pragmatic Comparison - Dezaye, Dlkhosh J.H. (Humanities Journal of University of Zakho, 2015)
This paper deals with the deictic expressions and their uses by the traditional and modern scholars. It is axiomatic that any use of language takes the speaker’s spatiotemporal location as the centre of the speech event. Based on this, there are five types of deixis: (1) personal, (2) spatial, (3) temporal, (4), social, and (5) discoursal. The paper aims at tracing the development in the use of these concepts by the traditional Arab scholars, who realized the importance of these concepts in meaning construction in the course of dealing with different syntactic and semantic phenomena, e.g., they referred to such concepts in explaining the use of pronouns, demonstratives, relative pronouns, place and time adverbials, etc. Those were all subsumed under what they would term ’vague expressions’, which they defined as context-dependent expressions whose meanings pertain to the speaker’s location, let alone the hearer’s location and the linguistic context. The paper consists of five sections. Each section deals with a type of deixis as viewed by the traditional and moderns scholars. Texts exemplifying the views of both schools are provides. Finally, the paper ends with the most important conclusions drawn from the analyses in the five sections.